Technology, Work and Leisure : Reflections on the Gains and Costs of Abundance - Wilensky, Harold (Relations industrielles / Industrial Relations, 1967)
A technology that permits a heavy flow of military and consumer goods, a mass education system producing a mass audience, untrained to higher tastes, a cultural élite more heterogeneous in background and functions, more open to mass culture, these are all gains of abundance, but to what cost ? The following text is drawn from an address presented at the last meeting of CIRRI and from the discussion which took place.